Atmospheric oxidation of methyl and ethyl tert-butyl ethers initiated by hydroxyl radicals. A quantum chemistry study. (1st November 2015) - Iuga, Cristina; Osnaya-Soto, Liliana; Ortiz, Elba; Vivier-Bunge, Annik
Graphical abstract: Highlights: We studied the reactions of MTBE and ETBE with OH radicals in the gas phase, using quantum chemistry methods. The potential energy surfaces were obtained at the M06-2X/6-311++G(d, p) level. The calculated rate constants reproduce remarkably well the available experimental data. In the gas phase, ETBE reacts more than 2 times faster with OH radicals than MTBE. The H atoms that are most easily abstracted are the ones occupying an α position with respect to the ether oxygen atom. Abstract: In this work, a systematic investigation on the reactions of methyl t - butyl ether (MTBE) and ethyl t - butyl ether (ETBE) with OH radicals in the gas phase has been performed, within the Density Functional (DFT) framework. The potential energy surfaces were obtained at the M06-2X/6-311++G(d, p) level. Specific emphasis was given to obtain kinetic data for MTBE and ETBE oxidative degradation and to identify and quantify the intermediate products formed. The values of the calculated rate constants reproduce remarkably well the available experimental data. The calculated total rate constants for the MTBE +  OH and ETBE +  OH reactions, in the gas phase at 298.15 K, are 2.79 × 10 −12 and 7.38 × 10 −12  cm 3  molecules −1  s −1 . Thus, ETBE reacts more than 2 times faster with OH radicals than MTBE. In both molecules, the hydrogen atoms that are most easily abstracted are the ones occupying an α position with respect to the ether oxygen atom. The contribution of the reaction channels involving H-abstraction from the tert - butyl group amounts to about 24–27% of the total rate coefficient. The results obtained in this work may improve the reliability and precision of the OH radical kinetic data required to predict the lifetime of aliphatic ethers and their contribution to urban and regional pollution.